Realistic environmental exposure to microplastics does not induce biological effects in the Pacific oyster Crassostrea gigas. (January 2020) - Revel, Messika; Châtel, Amélie; Perrein-Ettajani, Hanane; Bruneau, Mélanie; Akcha, Farida; Sussarellu, Rossana; Rouxel, Julien; Costil, Katherine; Decottignies, Priscilla; Cognie, Bruno; Lagarde, Fabienne; Mouneyrac, Catherine
Abstract: The aim of the present study was to evaluate the presence and potential toxic effects of plastic fragments (<400 μm) of polyethylene and polypropylene on the Pacific oyster Crassostrea gigas. Oysters were exposed to environmentally relevant concentrations (0, 0.008, 10, 100 μg of particles/L) during 10 days, followed by a depuration period of 10 days in clean seawater. Effects of microplastics were evaluated on the clearance rate of organisms, tissue alteration, antioxidant defense, immune alteration and DNA damage. Detection and quantification of microplastics in oyster's tissues (digestive gland, gills and other tissues) and biodeposits using infrared microscopy were also conducted. Microplastics were detected in oyster's biodeposits following exposure to all tested concentrations: 0.003, 0.006 and 0.05 particles/mg of biodeposits in oysters exposed to 0.008, 10 and 100 μg of particles/L, respectively. No significant modulation of biological markers was measured in organisms exposed to microplastics in environmentally relevant conditions. Highlights: No detection of microplastics in oysters' tissues. Identification of microplastics in biodeposits of oysters. No effects of microplastics on oxidative stress, DNA damage or immune marker. No effects of microplastics on oyster physiology and tissue integrity.